Empowerment of Goat Farmers through the Doctoral Service Program in Mount Kawi Area, Wonosari District, Malang Regency - Ciptadi, Gatot; Adelina Ari Hamiyanti; Wresti Listu Anggayasti; Dyah Kinasih Wuragil Putu Raharjo; Agus Budiarto; Khonita Rahma Diani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Goat farming in Wonosari District, Malang Regency, presents significant potential; however, local farmers face numerous challenges, including livestock management, record-keeping, feed quality, hygienic milking practices, marketing, and organizational issues. This 2024 Doctoral Service Program (DM) by Universitas Brawijaya aims to enhance the welfare of farmers by optimizing production management, improving milk quality, expanding marketing reach, and strengthening cooperative management. Specifically, the program seeks to increase the quantity and quality of goat milk production, improve farmer knowledge and skills in farm management and hygienic practices, and develop digital and conventional marketing strategies. Methods employed include training on feed formulation using local resources, hygienic milking practices, milk quality control, and online and offline marketing platforms. The outcomes demonstrate that the program enhanced goat milk production and quality, improved farmer knowledge and skills, expanded market access, and strengthened the cooperative’s operational structure. Post-test results showed significant improvements in farmers' abilities in feed formulation, hygienic milking, and marketing strategies. This indicates that the program effectively elevated practical skills, contributing to increased productivity, product competitiveness, and the economic empowerment of the local farming community.